[D-Ala2]deltorphin I binding and pharmacological evidence for a special subtype of delta opioid receptor on human and invertebrate immune cells. - Stefano, G B (1992)
The effects of the opioid neuropeptide [D-Ala2]deltorphin I, isolated from amphibian skin, on immunoregulatory activities were studied in representatives of vertebrates and invertebrates. The high potency of this compound parallels that of [Met]enkephalin, which was previously demonstrated in vertebrate plasma and invertebrate hemolymph. The addition of [D-Ala2]deltorphin I at 10(-11) M to human granulocytes or immunocytes of the mollusc Mytilus edulis resulted in cellular adherence and conformational changes indicative of cellular activation. This value is in line with the concentrations obtained with [Met]enkephalin, tested in the presence of the specific neutral endopeptidase 24.11 inhibitor phosphoramidon, and this opioid's synthetic analog [D-Ala2, Met5]enkephalin which, like [D-Ala2]deltorphin I, is resistant to proteolytic degradation. Both ligands appear to be acting on the same population of immunocytes. The same relationship was estimated to exist in the insect Leucophaea maderae, in which the high viscosity of the hemolymph makes the quantification of reactive cells more difficult than in Mytilus. In addition, [D-Ala2]deltorphin I is as potent as beta-endorphin in affecting the proliferation of lymphocytes in response to mitogen. Saturation experiments with unlabeled ligands and the radioligands [3H][D-Ala2]deltorphin I and [3H][D-Ala2,Met5]enkephalinamide revealed the presence of two high-affinity binding sites on human granulocytes, one sensitive to the nonequilibrium delta opioid antagonist [D-Ala2,Leu5,Cys6]enkephalinamide and the other relatively insensitive. The results obtained with [D-Ala2]deltorphin I support the view that the special role played by endogenous [Met]enkephalin in immunobiological activities of vertebrates and invertebrates is mediated by a special subtype of delta opioid receptor.